2022
DOI: 10.1155/2022/4875799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender on Serum Leptin in Type 2 Diabetes Mellitus: A System Review and Meta-Analysis

Abstract: Objective. To assess the effect of gender factors on serum leptin levels in patients with diabetes mellitus. Methods. To remove any studies that indicated a relationship between leptin-based inflammatory variables and the prevalence of type 2 diabetes in particular patient categories, a comprehensive search of all articles published between July 2019 and June 2021 was performed on PubMed/MEDLINE, Web of Science, Scopus, and EBSCO Host, including Academic Search Premier, Africa-Wide Information, and Cumulative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Leptin was also higher in T2DM patients with diabetic complications [172,173]. Although some studies suggested a difference in leptin concentrations between men and women [174,175], a recent meta-analysis of 10 studies with more than thirty thousand diabetic participants in total concluded gender factors did not affect leptin levels in T2DM patients [176]. In addition, many other factors may influence leptin levels in T2DM patients, for example, some anti-diabetic medications [177,178].…”
Section: Diabetes and Adipokinesmentioning
confidence: 99%
“…Leptin was also higher in T2DM patients with diabetic complications [172,173]. Although some studies suggested a difference in leptin concentrations between men and women [174,175], a recent meta-analysis of 10 studies with more than thirty thousand diabetic participants in total concluded gender factors did not affect leptin levels in T2DM patients [176]. In addition, many other factors may influence leptin levels in T2DM patients, for example, some anti-diabetic medications [177,178].…”
Section: Diabetes and Adipokinesmentioning
confidence: 99%